Search for heavy neutral and charged leptons in e+e− annihilation at LEP - Dova, María Teresa (2001)
A search for exotic unstable neutral and charged heavy leptons as well as for stable charged heavy leptons is performed with the L3 detector at LEP. Sequential, vector and mirror natures of heavy leptons are considered. No evidence for their existence is found and lower limits on their masses are set.